Analisis Proses Pemecahan Masalah Geometri Berdasarkan Teori Van Hiele - Marlinda Indah Eka Budiarti (Universitas Muhammadiyah Sorong, 2016)
AbstractThis study aims to explore and describe the process of problem solving geometry reach the level of visualization based on the Van Hiele theory. This type of research is descriptive explorative and qualitative approach. Subject of the study was obtained from the high school students who were tested on the level of Van Hiele geometry. Each level of visualization. The results of this study indicate that solving problems in geometry learners who attained think visualization is to identify problems and set goals using the language question.Â